Liquid titanium catalyst as well as preparation method and application thereof
By reacting tetraisopropyl titanate, organosilicate and hydroxycarboxylic acid in an alcohol solvent, and adding antioxidants and metal acetates, a stable liquid titanium catalyst was prepared, which solved the color instability and hydrolysis problems of existing titanium catalysts in the synthesis of biodegradable polyester, and achieved efficient and stable catalytic effects.
Patent Information
- Application Number
- CN202411744666.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-03-04
AI Technical Summary
The existing titanium-based catalysts have color powder or redness when preparing biodegradable polyesters, poor product quality stability and catalyst hydrolysis, which limits their application.
Tetraisopropyl titanate, organosilicate, hydroxycarboxylic acid and anti-hydrolyzer are used to react in an alcohol solvent, and antioxidant, phosphate and metal acetate are added, and small molecules are removed through high-temperature reaction to prepare a stable liquid titanium catalyst.
The prepared liquid titanium catalyst has stable properties, is not hydrolyzed, can be stored for a long time, and has excellent catalytic properties in the synthesis of biodegradable polyesters, improving the color and quality stability of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal catalysts and relates to a titanium catalyst, in particular to a liquid titanium catalyst and a preparation method and application thereof. Background Art
[0002] Biodegradable polyesters such as polybutylene terephthalate-adipate (PBAT), polybutylene succinate (PBS), polybutylene succinate-adipate (PBSA), polybutylene terephthalate-succinate (PBST) are currently widely used biodegradable polyesters at home and abroad. Compared with traditional plastics such as PE and PET, biodegradable polyesters can be completely degraded into water and carbon dioxide under certain conditions. They are typical environmentally friendly materials and play an irreplaceable role in solving white pollution. They can also be widely used in biodegradable products such as shopping bags, garbage bags, agricultural mulch films, textiles, injection molded parts, etc.
[0003] At present, the catalysts used for biodegradable polyesters on the market are mainly titanium-based catalysts. The titanium-based catalysts used in the early days were organic esters (such as tetramethyl titanate, tetraethyl titanate, tetrabutyl titanate, tetraisopropyl titanate, tetra-n-propyl titanate, bis(acetylacetonato) diisopropyl titanate, etc.). The problems are that the obtained biodegradable polyester products are powdery or reddish in color, the product quality stability is poor, and the catalyst has different degrees of hydrolysis in the esterification process of the polyester device, so its application is subject to certain restrictions.
[0004] Complex titanium catalysts have become a research hotspot for biodegradable polyester catalysts in recent years due to their high activity and lack of heavy metals. Many domestic companies and research institutions have also carried out research and application of new titanium biodegradable polyester catalysts, hoping to modify traditional titanium catalysts and develop new titanium catalysts that are highly active, environmentally friendly and can overcome the shortcomings of traditional titanium catalysts, so as to promote the sustainable development of the biodegradable polyester industry.
[0005] Patent application CN101270185A discloses a method for preparing a liquid titanium catalyst for preparing polyester and copolyester, the steps of which are: reacting n-butyl titanate, ethylene glycol, ethyl orthosilicate and a metal promoter in a solvent, removing small molecules, and then adding a complexing agent to react to obtain a liquid titanium catalyst. However, the patent application uses n-butyl titanate as the starting material, and butanol is produced in the reaction. Its high boiling point leads to a slow reaction rate with the complexing agent during the catalyst preparation process, and the reaction is not complete, which affects the activity of the catalyst; at the same time, since ethylene glycol is added in the first step to participate in the reaction, the trace impurities contained in the ethylene glycol will coordinate the titanium element with it, making the catalyst appear light yellow to yellow, and the color becomes darker when exposed to light, which affects the color of the polyester product when it is used as a catalyst, producing an undesirable effect. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing a liquid titanium-based catalyst.
[0007] A second object of the present invention is to provide a liquid titanium-based catalyst prepared by the above preparation method.
[0008] The third object of the present invention is to provide the application of the above-mentioned liquid titanium-based catalyst.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] In a first aspect, the present invention provides a method for preparing a liquid titanium-based catalyst, comprising the following steps:
[0011] (A) tetraisopropyl titanate, organic silicon ester, hydroxycarboxylic acid, and anti-hydrolysis agent are added to an alcohol solvent and reacted at a temperature of 25 to 80° C. for 1 to 24 hours, wherein the organic silicon ester has a general formula of Si(OR)4, and R is an alkyl group selected from 1 to 4 carbon atoms; the molar ratio of tetraisopropyl titanate to organic silicon ester is 30:1 to 1:1, the molar ratio of tetraisopropyl titanate to hydroxycarboxylic acid is 1:10 to 10:1, the molar ratio of tetraisopropyl titanate to anti-hydrolysis agent is 1:10 to 10:1, and the molar ratio of tetraisopropyl titanate to alcohol solvent is 1:1 to 1:50;
[0012] (B) adding an antioxidant, a phosphate and a metal acetate to the reaction product of step (A), reacting at a temperature of 100 to 200° C. for 1 to 48 hours, removing small molecules, and obtaining a liquid titanium catalyst; wherein the metal acetate is selected from one or more of sodium acetate, magnesium acetate, aluminum acetate, calcium acetate, zinc acetate, and cobalt acetate, the molar ratio of tetraisopropyl titanate to the antioxidant is 1:10 to 10:1, and the molar ratio of tetraisopropyl titanate to the metal element in the metal acetate is 20:1 to 5:1.
[0013] Preferably, the organic silicon ester is selected from at least one of tetramethyl silicate, tetraethyl silicate and tetrabutyl silicate.
[0014] Preferably, the hydroxycarboxylic acid is selected from at least one of citric acid, tartaric acid, lactic acid and malic acid.
[0015] Preferably, the anti-hydrolysis agent is selected from at least one of monomer carbodiimide and styrene-acrylonitrile-glycidyl methacrylate.
[0016] Preferably, the antioxidant is selected from at least one of antioxidant TPP, antioxidant TNP, antioxidant 1010, antioxidant 1076, and antioxidant DLTP.
[0017] Preferably, the alcohol solvent is selected from ethanol, isopropanol, 1,4-butanediol or a mixture of two or more thereof.
[0018] Preferably, the phosphate ester is selected from at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate and triphenyl phosphate.
[0019] Preferably, the molar ratio of tetraisopropyl titanate to organic silicone ester is 20:1 to 1:1, the molar ratio of tetraisopropyl titanate to hydroxycarboxylic acid is 1:10 to 10:1, the molar ratio of tetraisopropyl titanate to anti-hydrolysis agent is 1:10 to 10:1, the molar ratio of tetraisopropyl titanate to alcohol solvent is 1:1 to 1:15, the molar ratio of tetraisopropyl titanate to antioxidant is 1:10 to 1:1, and the molar ratio of tetraisopropyl titanate to the metal element is 10:1 to 5:1.
[0020] In a second aspect, the present invention provides a liquid titanium-based catalyst prepared by the above preparation method.
[0021] In a third aspect, the present invention also provides the use of the liquid titanium catalyst in the production of biodegradable polyester products. The synthesized biodegradable polyester products can be used for agricultural films, shopping bags, garbage bags, etc.
[0022] The preparation method of biodegradable polyester is as follows:
[0023] The first step: esterification reaction of terephthalic acid and adipic acid, or terephthalic acid and succinic acid, or terephthalic acid and sebacic acid with 1,4-butanediol at 210°C to 230°C and normal pressure to obtain a prepolymer;
[0024] Step 2: polycondensation reaction is carried out under high vacuum conditions, with a reaction temperature of 220-245°C and a pressure lower than 150 Pa. The catalyst can be added during the addition of the first step or before the decompression operation of the second step.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The catalyst of the present invention is prepared by reacting titanium as the main catalyst with hydroxycarboxylic acid in an alcohol solvent, adding an organic silicon ester to introduce silicon, adding an antioxidant, a phosphate ester and another metal acetate to the obtained reaction intermediate for further reaction, and heating to remove small molecules. The liquid catalyst is stable in nature, does not hydrolyze, and can be stored stably for a long time.
[0027] 2. The catalyst can be added directly or diluted and dissolved in BDO and then added to the raw materials for synthesizing biodegradable polyester (such as terephthalic acid, adipic acid, succinic acid, sebacic acid) to be used as a biodegradable polyester catalyst. The catalyst addition amount (based on the mass ratio of the contained titanium atoms to the total acid required to produce one ton of biodegradable polyester products) is 100×10-6 ~300×10 -6 . DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a liquid titanium-based catalyst, comprising the following steps:
[0029] (A) tetraisopropyl titanate, organic silicon ester, hydroxycarboxylic acid, and anti-hydrolysis agent are added to an alcohol solvent and reacted at a temperature of 25 to 80° C. for 1 to 24 hours, wherein the organic silicon ester has a general formula of Si(OR)4, and R is an alkyl group selected from 1 to 4 carbon atoms; the molar ratio of tetraisopropyl titanate to organic silicon ester is 30:1 to 1:1, the molar ratio of tetraisopropyl titanate to hydroxycarboxylic acid is 1:10 to 10:1, the molar ratio of tetraisopropyl titanate to anti-hydrolysis agent is 1:10 to 10:1, and the molar ratio of tetraisopropyl titanate to alcohol solvent is 1:1 to 1:50;
[0030] (B) adding an antioxidant, a phosphate compound and a metal acetate to the reaction product of step (A), reacting at a temperature of 100 to 200° C. for 1 to 48 hours, removing small molecules, and obtaining a liquid titanium catalyst; wherein the metal acetate is selected from one or more of sodium acetate, magnesium acetate, aluminum acetate, calcium acetate, zinc acetate, and cobalt acetate, the molar ratio of tetraisopropyl titanate to the antioxidant is 1:10 to 10:1, and the molar ratio of tetraisopropyl titanate to the metal element in the metal acetate is 20:1 to 5:1.
[0031] In a specific embodiment, the organic silicon ester is selected from at least one of tetramethyl silicate, tetraethyl silicate and tetrabutyl silicate.
[0032] In a specific embodiment, the hydroxycarboxylic acid is selected from at least one of citric acid, tartaric acid, lactic acid and malic acid.
[0033] In a specific embodiment, the anti-hydrolysis agent is selected from at least one of monomer carbodiimide and styrene-acrylonitrile-glycidyl methacrylate.
[0034] In a specific embodiment, the antioxidant is selected from at least one of antioxidant TPP, antioxidant TNP, antioxidant 1010, antioxidant 1076, and antioxidant DLTP.
[0035] In a specific embodiment, the alcohol solvent is one or a mixture of two or more of ethylene glycol, isopropanol, and 1,4-butanediol.
[0036] In a specific embodiment, the phosphate ester is selected from at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate, and triphenyl phosphate.
[0037] The present invention is further described in detail below with reference to specific embodiments.
[0038] Example 1
[0039] Add 56.8g of tetraisopropyl titanate (0.2mol), 4.2g of tetraethyl silicate (0.02mol), 0.63g of carbodiimide (0.02mol) and 100g of anhydrous ethanol to a three-necked flask equipped with an electric stirrer, a dropping funnel and a spherical condenser, and mix them evenly. Slowly drip a mixed solution of 84.4g of citric acid monohydrate (0.3mol) and 200g of ethanol into the three-necked flask. After the addition is completed, heat the mixture from room temperature to 65°C and react for 3 hours. A white precipitate is precipitated, and 2.7g of sodium acetate (0.02mol) and 42g of trimethyl phosphate (0.3mol) are added continuously. 11.8g of antioxidant 1010 (0.01mol) are reacted at 100-200°C for 4 hours to remove small molecules until the system becomes a homogeneous liquid to obtain catalyst A.
[0040] Preparation of polyester
[0041] 13.1 kg of adipic acid (AA), 24 kg of 1,4-butanediol (BDO), 13.54 kg of terephthalic acid (PTA) and catalyst A (based on the amount of biodegradable polyester produced, the weight content of titanium atoms is 150×10 -6 ), add 100L polymerization reactor. Esterification reaction is carried out at 210℃~230℃ and normal pressure. When the amount of distilled water reaches more than 95% of the theoretical value, esterification is completed. At this time, the temperature of the reaction system is 220~230℃. The pressure is gradually reduced and vacuumed to about 1000Pa within half an hour, and the reaction is continued for 1h. Then, the vacuum is continued to be evacuated to 150pa and the polymerization reaction is carried out at 230~245℃. The reaction is stopped after the polycondensation product reaches the required melting point (that is, the agitator current reaches a certain value). After that, the reaction product is continuously extruded in strips from the bottom of the polymerization reactor through nitrogen, cooled in a water tank, pelletized and dried.
[0042] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0043] Example 2
[0044] Add 56.8g of tetraisopropyl titanate (0.2mol), 3.04g of tetramethyl silicate (0.02mol), 0.95g of carbodiimide (0.03mol) and 100g of 1,4-butanediol to the three-mouth equipped with an electric stirrer, a dropping funnel and a spherical condenser, and mix them evenly. Slowly drip a mixed solution of 84.4g of citric acid monohydrate (0.3mol) and 200g of methanol into the three-mouth. After the addition is completed, heat the mixture from room temperature to 65°C and react for 3 hours. A white precipitate is precipitated, and 3.1g of magnesium acetate (0.02mol) and 54.6g of triethyl phosphate (0.3mol) are added, and 17.7g of antioxidant 1010 (0.15mol) are reacted at 100-200°C for 1-4 hours to remove small molecules until the system becomes a homogeneous liquid to obtain catalyst B.
[0045] Preparation of polyester
[0046] Polyester was prepared in the same manner as in Example 1, using Catalyst B as the catalyst (based on the amount of biodegradable polyester produced, the weight content of titanium atoms was 150×10 -6 ).
[0047] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0048] Example 3
[0049] Add 56.8g of tetraisopropyl titanate (0.2mol), 6.3g of tetraethyl silicate (0.03mol), 0.63g of carbodiimide (0.02mol) and 100g of 1,4-butanediol to a three-necked flask equipped with an electric stirrer, a dropping funnel and a spherical condenser, and mix them evenly. Slowly drip a mixed solution of 84.4g of citric acid monohydrate (0.3mol) and 200g of methanol into the three-necked flask. After the addition is completed, heat the mixture from room temperature to 65°C and react for 3 hours. A white precipitate is precipitated, and 3.67g of zinc acetate (0.02mol) and 97.8g of triphenyl phosphate (0.3mol) are added continuously. 11.8g of antioxidant 1010 (0.01mol) are reacted at 100-200°C for 1-4 hours to remove small molecules until the system becomes a homogeneous liquid to obtain catalyst C.
[0050] Preparation of polyester
[0051] The polyester was prepared in the same manner as in Example 1, using Catalyst C as the catalyst (based on the amount of biodegradable polyester produced, the weight content of titanium atoms was 150×10 -6 ).
[0052] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0053] Example 4
[0054] Add 56.8g of tetraisopropyl titanate (0.2mol), 6.41g of butyl orthosilicate (0.02mol), 0.63g of carbodiimide (0.02mol) and 100g of anhydrous ethanol to a three-necked flask equipped with an electric stirrer, a dropping funnel and a spherical condenser, and mix them evenly. Slowly drip a mixed solution of 56.3g of citric acid monohydrate (0.2mol) and 200g of ethanol into the three-necked flask. After the addition is completed, heat the mixture from room temperature to 78°C and react for 3 hours. A white precipitate is precipitated, and 4.08g of aluminum acetate (0.02mol) and 79.9g of tributyl phosphate (0.3mol) are added, and 3.13g of antioxidant TPP (0.01mol) are reacted at 100-200°C for 1-4 hours to remove small molecules until the system becomes a homogeneous liquid to obtain catalyst D.
[0055] Preparation of polyester
[0056] The polyester was prepared in the same manner as in Example 1, using Catalyst D as the catalyst (based on the amount of biodegradable polyester produced, the weight content of titanium atoms was 150×10 -6 ).
[0057] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0058] Example 5
[0059] Add 56.8g of tetraisopropyl titanate (0.2mol), 2.1g of tetraethyl silicate (0.01mol), 0.32g of carbodiimide (0.01mol) and 100g of anhydrous ethanol to a three-necked flask equipped with an electric stirrer, a dropping funnel and a spherical condenser, and mix them evenly. Slowly drip a mixed solution of 84.4g of citric acid monohydrate (0.3mol) and 200g of ethanol into the three-necked flask. After the addition is completed, heat the mixture from room temperature to 78°C and react for 3 hours. A white precipitate is precipitated, and 4.74g of calcium acetate (0.03mol) and 54.6g of triethyl phosphate (0.3mol) are added continuously. 5.3g of antioxidant 1076 (0.01mol) are reacted at 100-200°C for 1-4 hours to remove small molecules until the system becomes a homogeneous liquid to obtain catalyst E.
[0060] Preparation of polyester
[0061] The polyester was prepared in the same manner as in Example 1, using Catalyst E as the catalyst (based on the amount of biodegradable polyester produced, the weight content of titanium atoms was 150×10 -6 ).
[0062] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0063] Example 6
[0064] Add 56.8g of tetraisopropyl titanate (0.2mol), 8.4g of tetraethyl silicate (0.04mol), 1.26g of carbodiimide (0.04mol) and 100g of isopropanol to a three-necked flask equipped with an electric stirrer, a dropping funnel and a spherical condenser, and mix them evenly. Slowly drip a mixed solution of 84.4g of citric acid monohydrate (0.3mol) and 200g of ethanol into the three-necked flask. After the addition is completed, heat the mixture from room temperature to 78°C and react for 3 hours. A white precipitate is precipitated, and 3.54g of cobalt acetate (0.02mol) and 54.6g of triethyl phosphate (0.3mol) are added continuously. 11.8g of antioxidant 1010 (0.01mol) are reacted at 100-200°C for 1-4 hours to remove small molecules until the system becomes a homogeneous liquid to obtain catalyst F.
[0065] Preparation of polyester
[0066] Polyester was prepared in the same manner as in Example 1, using Catalyst F as the catalyst (based on the amount of biodegradable polyester produced, the weight content of titanium atoms was 150×10 -6 ).
[0067] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0068] Comparative Example 1
[0069] The biodegradable polyester was prepared in the same manner as in Example 1, using 56.8 g of tetraisopropyl titanate and 42 g of trimethyl phosphate as catalysts (based on the titanium atom weight content of the generated biodegradable polyester being 150×10 -6 ).
[0070] The obtained PBAT product was subjected to performance testing, and the analysis results are shown in Table 1.
[0071] In the present invention, the melt index, terminal carboxyl group, hue, mechanical properties, etc. of the biodegradable polyester are analyzed and tested by the following methods:
[0072] (1) Melt index: Weigh about 5 g of sliced sample and measure it using a MFI-3322 melt flow rate instrument (manufactured by Chengde Jinjian Testing Instrument Co., Ltd.).
[0073] (2) Terminal carboxyl content: Using the titration analysis method, 0.8-1.2 g of slice sample was dissolved in a mixed solution of phenol / chloroform (volume ratio of 2:3), and titrated with a sodium hydroxide-ethanol standard solution.
[0074] (3) Hue a value: measured using a WSC-S fully automatic colorimeter.
[0075]
[0076]
[0077] Combining the physical and chemical properties of Examples 1-6 and Comparative Example 1, it can be seen that the biodegradable polyester synthesized under the action of the liquid titanium catalyst prepared by the present invention has a high melt index and a terminal carboxyl content of less than 20 mol / t, indicating a high molecular weight. As shown in Table 1, when the liquid titanium catalyst AF in the present invention is used, Examples 1-6 can prepare PBAT products with excellent properties.
[0078] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a liquid titanium-based catalyst, characterized in that: The following steps are involved: (A) tetraisopropyl titanate, organic silicon ester, hydroxycarboxylic acid, and anti-hydrolysis agent are added to an alcohol solvent and reacted at a temperature of 25 to 80° C. for 1 to 24 hours, wherein the organic silicon ester has a general formula of Si(OR)4, and R is an alkyl group selected from 1 to 4 carbon atoms; the molar ratio of tetraisopropyl titanate to organic silicon ester is 30:1 to 1:1, the molar ratio of tetraisopropyl titanate to hydroxycarboxylic acid is 1:10 to 10:1, the molar ratio of tetraisopropyl titanate to anti-hydrolysis agent is 1:10 to 10:1, and the molar ratio of tetraisopropyl titanate to alcohol solvent is 1:1 to 1:50; (B) adding an antioxidant, a phosphate compound and a metal acetate to the reaction product of step (A), reacting at a temperature of 100 to 200° C. for 1 to 48 hours, removing small molecules, and obtaining a liquid titanium catalyst; wherein the metal acetate is selected from one or more of sodium acetate, magnesium acetate, aluminum acetate, calcium acetate, zinc acetate, and cobalt acetate, the molar ratio of tetraisopropyl titanate to the antioxidant is 1:10 to 10:1, and the molar ratio of tetraisopropyl titanate to the metal element in the metal acetate is 20:1 to 5:
1.
2. The method for preparing a liquid titanium-based catalyst according to claim 1, characterized in that: The organic silicon ester is selected from at least one of tetramethyl silicate, tetraethyl silicate and butyl orthosilicate.
3. The method for preparing a liquid titanium catalyst according to claim 1, characterized in that: The hydroxycarboxylic acid is selected from at least one of citric acid, tartaric acid, lactic acid and malic acid.
4. The method for preparing a liquid titanium-based catalyst according to claim 1, characterized in that: The anti-hydrolysis agent is selected from at least one of monomer carbodiimide and styrene-acrylonitrile-glycidyl methacrylate.
5. The method for preparing a liquid titanium-based catalyst according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant TPP, antioxidant TNP, antioxidant 1010, antioxidant 1076, and antioxidant DLTP.
6. The method for preparing a liquid titanium catalyst according to claim 1, characterized in that: The alcohol solvent is selected from ethanol, isopropanol, 1,4-butanediol or a mixture of two or more thereof.
7. The method for preparing a liquid titanium-based catalyst according to claim 1, characterized in that: The phosphate ester is selected from at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate and triphenyl phosphate.
8. The method for preparing a liquid titanium-based catalyst according to claim 1, characterized in that: The molar ratio of tetraisopropyl titanate to organic silicon ester is 20:1-1:1, the molar ratio of tetraisopropyl titanate to hydroxycarboxylic acid is 1:10-10:1, the molar ratio of tetraisopropyl titanate to anti-hydrolysis agent is 1:10-10:1, the molar ratio of tetraisopropyl titanate to alcohol solvent is 1:1-1:15, the molar ratio of tetraisopropyl titanate to antioxidant is 1:10-1:1, and the molar ratio of tetraisopropyl titanate to the metal element is 10:1-5:
1.
9. A liquid titanium catalyst, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Use of the liquid titanium catalyst according to claim 9 in the production of biodegradable polyester products.
Citation Information
Patent Citations
Process for preparing liquid condition titanium catalyst for preparing polyester and copolyester
CN101270185A
Cited By
Method for synthesizing poly (butylene adipate-co-terephthalate) by one-step method
CN120623453A
Liquid titanium-based polyester catalyst and method for preparing the same
CN122647533A